PENGARUH SISTEM PENILAIAN KINERJA TERHADAP KINERJA PNS SATUAN KERJA PERANGKAT DAERAH KOTA BANDUNG DENGAN CONTRACTIBILITY SEBAGAI VARIABEL MODERATING - Nunik Lestari Dewi; Mathius Tandiontong; Selma Aghnia Vira (Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2018)
This study aims to determine the effect of performance appraisal system on the performance of civil servants Satuan Kerja Kota Bandung with contractibility as a moderating variable. Performance appraisal system in this research is divided into two variables: performance appraisal system oriented incentif / reward and performance appraisal system that oriented exploration. While the moderating variable is contractibility (performance agreement).The results showed that there is influence of performance appraisal system oriented incentives / rewards on the performance of civil servants SKPD Bandung of 75.2%. In addition, there is also the influence of exploration-oriented performance appraisal system on the performance of civil servants SKPD Bandung of 56.2%. The existence of the contractibility variable / performance agreement will strengthen the direct correlation of the independent variable to the dependent variable, so the result shows that there is influence of performance appraisal system oriented incentive / reward to the performance of civil servant SKPD Bandung with variable contractibility / performance agreement as moderating variable and there influence of performance appraisal system oriented exploration on the performance of civil servants SKPD Bandung with variable contractibility / performance agreement as a moderating variable.Keywords: incentive / reward oriented performance appraisal system, exploration-oriented performance appraisal system, contractibility (performance agreement), civil servant performance.